PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 25 PADANG - Nefira, Mutiara Rama; Basri, Irfani; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this study is three. First, describe the writing skills of exposition text of class VIII students of SMP Negeri 25 Padang before using discovery learning models assisted by audiovisual media. Second, describe the writing skills of exposition text of grade VIII students of SMP Negeri 25 Padang after using discovery learning models assisted by audiovisual media. Third, describe the influence of discovery learning models assisted by audiovisual media on writing exposition text skills of eighth grade students of SMP Negeri 25 Padang. The sample in this study was class VIII.2 with 29 students. The results of this study are three, namely as follows. First, exposition text writing skills before using the discovery learning learning model assisted by audiovisual media of eighth grade students of SMP Negeri 25 Padang are in almost adequate qualifications with an average value of 53.45. Second, the skill of writing exposition text after using the discovery learning model assisted by audiovisual media of eighth grade students of SMP Negeri 25 Padang is in a qualification of more than enough with an average score of 70.11. Third, based on the t-test, the alternative hypothesis (H_1) is received at a significant level of 95% and the degree of freedom (dk) = n-1 because of tcount> t table, which is 4.79> 1.70. This means that there is a significant influence on the use of discovery learning models assisted by audiovisual media on the exposition writing skills of eighth grade students at SMP Negeri 25 Padang.Â Kata kunci: Pengaruh, Discovery Learning, Keterampilan Menulis Teks EksposisiÂ